2022
DOI: 10.1155/2022/7130634
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQB1-AS1 Promotes Cell Proliferation, Inhibits Apoptosis, and Binds with ZRANB2 Protein in Hepatocellular Carcinoma

Abstract: Major histocompatibility complex, class II, DQ beta 1 antisense RNA 1 (HLA-DQB1-AS1) conferred the susceptibility to hepatocellular carcinoma. Sustaining cell growth and resisting apoptosis are two hallmarks of hepatocellular carcinoma. The present study explored the role of HLA-DQB1-AS1 in the proliferation and apoptosis of hepatocellular carcinoma cells and investigated its downstream pathway. Colony formation assay was performed to assess cell proliferation. Cell apoptosis was assessed with the TdT-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…These TNF-related lncRNAs were involved in carcinogenesis, and inflammatory and immune responses (22)(23)(24)(25). A number of studies have also demonstrated that some of TNF-related lncRNAs are closely associated with cancer proliferation and survival (32)(33)(34)(35)(36)(37)(38). Thus, we analyzed the expression patterns and clinical significance of TNFrelated lncRNAs in LUAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These TNF-related lncRNAs were involved in carcinogenesis, and inflammatory and immune responses (22)(23)(24)(25). A number of studies have also demonstrated that some of TNF-related lncRNAs are closely associated with cancer proliferation and survival (32)(33)(34)(35)(36)(37)(38). Thus, we analyzed the expression patterns and clinical significance of TNFrelated lncRNAs in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AC017100.1 was shown to be a protective factor for the prognosis of prostate cancer ( 35 ). HLA-DQB1-AS1 has been shown to interact with zinc finger RANBP2-type containing 2 (ZRANB2) protein to promote proliferation and inhibit apoptosis in hepatocellular carcinoma ( 36 ), suggest that higher expression of HLA-DQB1-AS1 might have a negative impact on survival in hepatocellular carcinoma, while it was demonstrated to be beneficial for the survival of patients with LUAD and melanoma ( 37 , 38 ). Therefore, the role of HLA-DQB1-AS1 in cancer was related to the type of cancers, and the mechanism needs to explore further.…”
Section: Discussionmentioning
confidence: 99%
“…In nucleotide analogs, naive patients with chronic HBV infection who have an AA genotype of the HLA-DQA1/DRB1 gene are more likely to develop HCC during entecavir treatment ( Kozuka et al, 2018 ). HLA-DQB1-AS1 can interact with ZRANB2 protein to promote cell proliferation and inhibit apoptosis in HCC ( Long et al, 2022 ). In addition, HLA-DQB1 polymorphisms increase the risk of HCC after hepatis C virus eradication ( Miki et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%